Mini-Course: From Virtual Reality to Augmented Reality – Fundamental Concepts and Applications - Dias, J. (Proceedings of the VII Symposium on Virtual Reality, SVR 2004, 2004)
Curso introdutório de Realidade Virtual e Realidade Aumentada